2011
DOI: 10.5296/ijafr.v1i1.949
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Workers’ Remittances on Private Investment and Total Consumption in Pakistan

Abstract: To check the two Objectives of the study one exploring the impact of work remittance on economic growth and second is Impact of work remittance on private investment and total consumption, 25 years’ time series data collected from the Economic survey of Pakistan for the time 1984-2009. The methodology used for the analysis, is Regression model so for regression we have used OLS (ordinary least square model).the work remittance has positively related with the Private investment and total consumption which resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 1 publication
8
19
0
Order By: Relevance
“…Yasmeen et al. () investigate the effect of workers' remittances on total consumption and private investment in Pakistan. Regression results indicate significant positive relationship of workers' remittances with both private investment and total consumption.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Yasmeen et al. () investigate the effect of workers' remittances on total consumption and private investment in Pakistan. Regression results indicate significant positive relationship of workers' remittances with both private investment and total consumption.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The country's reliance on foreign remittance is even increasing further because of the country's deteriorating export market as a result of its engagement in war on terror. Especially, the higher volumes of remittance positively contribute to a surge in private investment that leads to higher rate of economic growth in the country (Yasmeen et al, 2011). However, contrary to this, the finding of Rahman (2015) reveals that remittances have minimal impact on private investment but overall it has a positive impact on the economic growth.…”
Section: Asian Journal Of Economic Modellingmentioning
confidence: 98%
“…Some of the empirical findings by Griffith et al (2008); Okodua (2013); Yasmeen et al (2011);Malik (2013); Le (2011);Das (2009);Singh and Mehra (2014);Cherono (2013); Thagunna and Acharya (2013) and Akter (2016) suggested remittances inflow positively affect private investment, as an increase in remittances inflow leads to increase private investment. However, some of the studies by Rahman (2015) suggested minimal level of relationship between remittances inflow and private investment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…He suggested that workers' remittances have noteworthy positive effect on economic development in both short and long run. Yasmeen et al (2011) utilize the yearly time series information of period from 1984 to 2009 of Pakistan to distinguish the effect of workers' remittances on private venture and total expenditure. She found that workers' remittances have noteworthy positive effect on private investment and total utilization.…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 99%